2015
DOI: 10.1371/journal.pone.0127863
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Sunlight Reduces the Risk of Myopia in Rhesus Monkeys

Abstract: Exposure to sunlight has recently been postulated as responsible for the effect that more time spent outdoors protects children from myopia, while early life exposure to natural light was reported to be possibly related to onset of myopia during childhood. In this study, we had two aims: to determine whether increasing natural light exposure has a protective effect on hyperopic defocus-induced myopia, and to observe whether early postnatal exposure to natural light causes increased risk of refractive error in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 56 publications
(61 reference statements)
1
39
0
Order By: Relevance
“…It is noteworthy that the light intensity in this study was lower (1500-3300 lux) than in the other studies (10,000-40,000 lux), but similar to the intensity employed in the current study (i.e., 2500-5000 lux). 9,15,42,45 This difference may be a critical factor because there are numerous reports indicating that laboratory light intensity and duration are in fact contributing factors because they do affect FDM progression in animal studies. 6,8,[36][37][38] Our results agree other reports indicating that the intensity and duration of light exposure are contributing factors to FDM in mice.…”
Section: D1r (At Least Partially) Mediates Bl Inhibitory Effects On Rmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the light intensity in this study was lower (1500-3300 lux) than in the other studies (10,000-40,000 lux), but similar to the intensity employed in the current study (i.e., 2500-5000 lux). 9,15,42,45 This difference may be a critical factor because there are numerous reports indicating that laboratory light intensity and duration are in fact contributing factors because they do affect FDM progression in animal studies. 6,8,[36][37][38] Our results agree other reports indicating that the intensity and duration of light exposure are contributing factors to FDM in mice.…”
Section: D1r (At Least Partially) Mediates Bl Inhibitory Effects On Rmentioning
confidence: 99%
“…Other animal studies further indicated that laboratory bright light (BL) is a factor contributing to myopia inhibition in chicks, [10][11][12] guinea pigs, 13 and primates. 14,15 However, the underlying receptor-linked signaling mechanisms mediating such suppression require clarification. Dopamine (DA) is a retinal neurotransmitter released by dopaminergic amacrine cells (ACs).…”
mentioning
confidence: 99%
“…Furthermore, the light hypothesis, i.e. light-stimulated DA antagonizes myopia development (Rose et al, 2008) has been supported by a number of studies that show outdoor activity and/or bright light inhibits myopia, potentially through DA-mediated mechanisms (Ashby et al, 2009; Chen et al, 2017; Cohen et al, 2011; Cohen et al, 2012; Li et al, 2014; Morgan et al, 2012; Smith et al, 2012; Wang et al, 2015; Wu et al, 2013). The evidence from pharmacological and genetic studies has provided more details regarding how light or visual input controls retinal DA signaling and contributes to refractive development (for a recent review, see (Feldkaemper and Schaeffel, 2013)).…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53][54] In animal studies, experiments in chicken and nonhuman primate animal models have shown that high illuminance levels of light (>15,000 Lux) can slow or even stop the development of experimentally induced myopia. [65][66][67][68] Another hypothesis is that the pupillary miosis that occurs while viewing distant objects outdoors results in less image blur and peripheral hyperopic defocus. 69 Evidence from both animal and human studies has shown that ambient light exposure plays an important role in controlling eye growth.…”
Section: Solution 1: Early-stage Interventions: Outdoor Time To Prevementioning
confidence: 99%